Fluctuations and like-torque clusters at the onset of the discontinuous shear thickening transition in granular materials - S. H. E. Rahbari (Nature Portfolio, 2021)
An open question in the field of granular materials and non-equilibrium physics is the origin and interpretation of frictional effects and spatiotemporal fluctuation in the discontinuous shear thickening transition. Here, the authors study numerically the spatiotemporal fluctuations of local injected power across the discontinuous shear thickening transition, finding that rare fluctuations caused by frictional forces are governed by a simple fluctuation relation and the emergence of collective behavior in the particle’s torque.